2019
DOI: 10.4103/jips.jips_247_18
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparison of the effect of various surface treatments on the tensile bond strength of three different luting cement to zirconia copings

Abstract: Aim:The aim of this study was to evaluate and compare the tensile bond strength of zirconia copings subjected to three different surface treatment methods and cemented with three different luting agents.Materials and Methods:Seventy-two extracted maxillary premolar teeth were prepared to receive zirconia copings milled using computer-aided design/computer-aided manufacturing technology, which were divided into 9 groups of 8 specimens each. Three surface treatment protocols such as hydrofluoric acid etch treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The tensile bond strength of Zirconia with air abrasion shows a value of 2.71 ± 0.478, whereas when specimen were treated with HF acid they showed a tensile bond strength of 1.41 ± 0.338, and the third group surface treated with Al 2 O 3 particles followed by 30 µm silica coated Al 2 O 3 particles showed the value 4.22 ± 0.698. They concluded that air abrasion of the copings and META containing adhesive resin shows an increase in bond strength [16]. Visio.link is made up of MMA (Methyl methacrylate), PETIA (Pentacrythritoltriacrylate), dimethacrylate, and photoinitiator.…”
Section: Discussionmentioning
confidence: 99%
“…The tensile bond strength of Zirconia with air abrasion shows a value of 2.71 ± 0.478, whereas when specimen were treated with HF acid they showed a tensile bond strength of 1.41 ± 0.338, and the third group surface treated with Al 2 O 3 particles followed by 30 µm silica coated Al 2 O 3 particles showed the value 4.22 ± 0.698. They concluded that air abrasion of the copings and META containing adhesive resin shows an increase in bond strength [16]. Visio.link is made up of MMA (Methyl methacrylate), PETIA (Pentacrythritoltriacrylate), dimethacrylate, and photoinitiator.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] Different surface treatments showed success in improving the bond of Y-TZP to resin cements, with tribochemical silica coating showing better results when compared to other surface treatments such as air abrasion and acid etching. 7,[15][16][17][18] Several researches showed that the use of an MDP primer would have a positive impact on the initial shear bond strength (SBS) of the bonded zirconia samples. 7,11,14,16,17,[19][20][21][22][23][24][25] Although a high initial shear bond strength was achieved using a combination of surface treatments, priming agents and cements was successfully achieved 7,8,[14][15][16]26,27 , deterioration of the bond and significant decrease in the SBS was also noticed 7,8,14,23,25,28 Hence the need for testing different methods to maintain the original SBS or decrease the bond deterioration after aging was needed.…”
Section: Introductionmentioning
confidence: 99%